EKSTRAK DAUN KEMANGI (OCIMUM BASILICUM L) DAN MENURUNKAN KANDUNGAN COLIFORM PADA AIR BERSIH - Rahmatia Saleh; Jasman Jasman; Agnes Watung (POLTEKKES KEMENKES MANADO, 2018)
Extract is dry preparations, condensed or liquid made with menyari simplisia vegetable or animal according to a suitable manner, outside influences direct sunlight. Bacteria coliform are of bacteria intestinal, namely lives in the digestive tract man. Coliform bacteria indicators is the existence of bacteria patogenik other .The purpose of this research is to know extract basil leaves in lowering coliform on content clean water . This type of research is research quasi experiment with the use of the t-test , to know whether the trial of basil leaves extract (ocimum basilicium l) content can be lowered coliform on clean water . With treatment as many as 3 times and 3 times the repetition with the total sample of 12, kosentrasi used 2 percent , 4 % , 6 percent of and control . According to the research conducted sample of 12 and having 3 control and performed (3 repetition) that in concentration 2 % with control 1600 and dropped 540 , concentration 4 % experienced penurunan130 and concentration 6 % dropped 79 from the laboratory most effective kosentrasi % at 6 .Hopefully this research could add your next to researchers expected to add kosentrasi bacteria can coliform standard .